Revision of the genus Acallopistus Schoenherr (Coleoptera, Curculionidae, Curculioninae, Nerthopini) - Haran, Juilen (Zootaxa, 2013)
The genus Acallopistus (Curculioninae, Nerthopini) is revised. Eight species are recognized as valid: A. vellicosus Schoe-nherr, A. abutilonis Marshall, A. fallax Boheman, A. guttatus Boheman, A. crassirostris Hustache and three new species, A. dissimilis, A. hibisci and A. dentirostris. The following new synonymies are proposed: A. maculithorax Hustache and A. senegalensis Hustache = A. vellicosus Schoenherr, A. pardalis Gyllenhal= A. guttatus Boheman. Lectotypes are desig-nated for A. vellicosus Schoenherr, A. abutilonis Marshall, A. guttatus Boheman, A. crassirostris Hustache and A. malvae Boheman; one neotype is designated for A. fallax Boheman. The species A. malvae Boheman is excluded from the genus Acallopistus. A key to species, diagnosis of each species, together with habitus photographs and line illustrations of male and female genitalia are provided.